2014
DOI: 10.1186/1756-3305-7-169
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial dynamics of trypanosomes infecting the brush-tailed bettong (Bettongia penicillata): a cautionary note of disease-induced population decline

Abstract: BackgroundThe brush-tailed bettong or woylie (Bettongia penicillata) is on the brink of extinction. Its numbers have declined by 90% since 1999, with their current distribution occupying less than 1% of their former Australian range. Woylies are known to be infected with three different trypanosomes (Trypanosoma vegrandis, Trypanosoma copemani and Trypanosoma sp. H25) and two different strains of T. copemani that vary in virulence. However, the role that these haemoparasites have played during the recent decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 23 publications
3
45
1
Order By: Relevance
“…The PCR prevalence of T. vegrandis in koalas (13.6%) reported in the present study was at the lower end of prevalence estimates of T. vegrandis previously reported in woylies (14% -46%) [5,[15][16] and various other marsupial (up to 32%) [5] and bat species (88.9%)…”
Section: Accepted M Manuscriptcontrasting
confidence: 79%
See 1 more Smart Citation
“…The PCR prevalence of T. vegrandis in koalas (13.6%) reported in the present study was at the lower end of prevalence estimates of T. vegrandis previously reported in woylies (14% -46%) [5,[15][16] and various other marsupial (up to 32%) [5] and bat species (88.9%)…”
Section: Accepted M Manuscriptcontrasting
confidence: 79%
“…Of the eight native trypanosomes formerly described, only T. copemani and T. vegrandis species have been identified in multiple hosts, with the chronic effects of T. copemani infections possibly linked with the decline of woylie populations [5,16]. The current findings add more evidence to the fact that trypanosomes in Australian marsupials comprise a heterogeneous community, with low levels of host specificity and no evidence of restricted geographical distribution [1,4,5,[14][15][16][17].…”
Section: Accepted M Manuscriptmentioning
confidence: 54%
“…found that Clade A, including Trypanosoma copemani, appears more virulent and prevalent in a declining woylie population (Upper Warren, Western Australia) compared to a higher prevalence of less virulent clades in a stable population (Karakamia Wildlife Sanctuary, Western Australia) [15] . This observation has been further supported by a temporal association between decline patterns in the Upper Warren and T. copemani prevalence [16]. It has been suggested that woylies in the declining population may be less efficient at responding to more virulent genotypes of this endemic parasite [15].…”
Section: Introductionmentioning
confidence: 80%
“…We used an established and validated PCR protocol to detect Trypanosoma parasites in the blood stream of woylies [15,16,36]. DNA extraction and Trypanosoma PCR amplification were carried out as per previously described protocols [15,16,36].…”
Section: Dna Extraction and Pcr Amplification For Trypanosoma Speciesmentioning
confidence: 99%
See 1 more Smart Citation